2023
DOI: 10.1140/epjc/s10052-022-11152-9
|View full text |Cite
|
Sign up to set email alerts
|

Axion-like dark matter detection using Stern–Gerlach interferometer

Abstract: Quantum sensors based on the superposition of neutral atoms are promising for sensing the nature of dark matter (DM). In this study, we utilize the Stern–Gerlach (SG) interferometer configuration to seek a novel method for the detection of axion-like particles (ALPs). Using an SG interferometer, we create a spatial quantum superposition of neutral atoms such as $$^{3}$$ 3 He and $$^{87}$$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…Significant progress in quantum technology has opened avenues for utilizing it in various instruments to investigate ALP interactions. These include spin-precession instruments [30], electromagnetic squeezing [31][32][33], Stern-Gerlach interferometers [34], and spin-based amplifiers [35,36]. It has been shown that the ALP-photon interaction is enhanced in the presence of a magnetic field [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Significant progress in quantum technology has opened avenues for utilizing it in various instruments to investigate ALP interactions. These include spin-precession instruments [30], electromagnetic squeezing [31][32][33], Stern-Gerlach interferometers [34], and spin-based amplifiers [35,36]. It has been shown that the ALP-photon interaction is enhanced in the presence of a magnetic field [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%